Faith Lost: Faith Regained : Rediscovering a Transforming Christian Belief - Atkinson, James (Theological Seminar Series, 2005)
A holistic, positive answer to modernist and post-modernist challenges to Christian faith. Recent trends in theology have adapted to what has been assumed to be universally valid scientific thinking, thereby contributing to the erosion of traditional protestant belief. Pointing to parable as a tool of understanding and appealing to aesthetic appreciation as an analogy, the author makes an impassioned call for a return to an assured biblical faith. The answer lies in a fuller epistemology and a profounder ontology to explain the universe and man's place in it.